THE ROLE OF THE SCHOOL ENVIRONMENT IN SHAPING STUDENTS’ CHARACTER AT SMP IT ISP KARAWANG - Defrinal Hoerudin; Lusiana Rahmatiani; Fitri Silvia Sofyan (Journal Civics And Social Studies, 2026)
Character education is an essential aspect of the educational process because schools are not only responsible for transferring knowledge but also for shaping students’ attitudes, values, and behavior. This study aims to analyze the role of the school environment in shaping students’ character at SMP IT ISP Karawang and to identify the school environmental factors that significantly contribute to character formation. This research employed a qualitative descriptive approach. The research subjects included students, teachers, and the principal of SMP IT ISP Karawang. Data were collected through interviews, observation, and documentation, while data analysis was carried out through data reduction, data display, and conclusion drawing. The findings show that the school environment plays an important role in shaping students’ character through teacher role models, school discipline culture, religious habituation, positive social relationships among students, and extracurricular activities. These factors support the development of religious values, discipline, responsibility, social care, cooperation, tolerance, and empathy. The study also found that character formation at SMP IT ISP Karawang is strengthened through daily habituation, consistent supervision, moral guidance, and the integration of Islamic values into school activities. However, student discipline remains a challenge that requires continuous reinforcement. This study implies that a conducive, religious, and disciplined school environment can become an effective medium for strengthening students’ character.